Perancangan Interior Sneakers Addict Center di Surabaya - Sriti Mayang Sari, Stefanus Basoeki (Intra, 2014)
Sneakers are shoes made of rubber soles that have become a style now. Many people wear this shoes for their daily use to a variety of activities. By the time, kind of sneakers lovers community exploded in Indonesia, especially in Surabaya. These communities are found live in social network internet, there came a problem in this community that they doesnât have a real place that specifically accommodate the activities of sneakers lovers. Â The purpose of this interior design sneakers addict center is that sneakers lovers who had been living in the virtual world, now has a spesific place for their activities and make this facility as one of the icon places for sneakers lovers in Surabaya city that should be visited by the sneakers lovers from all over Indonesia, the concept Urban Authentic is connected with the history of sneakers and show up the authenticity of a brand image which is combined with industrial style. As expected that this facility could meet the needs and activities of sneakers lovers, especially in Surabaya.